2016
DOI: 10.1177/1948550616667617
|View full text |Cite
|
Sign up to set email alerts
|

The Liberal and Conservative Experience Across Academic Disciplines

Abstract: Inbar and Lammers asked members of APA Division 8 (personality and social psychology) about their political orientation, hostility experienced related to their political orientation, and their willingness to discriminate against others based on perceived political orientation. In this replication and extension, 618 faculty members from various academic disciplines across four California State University campuses completed an online questionnaire that added parallel questions about the liberal experience to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 34 publications
5
32
0
Order By: Relevance
“…We summarize additional studies here that were not included in their review as further evidence supporting their perspective. A replication and extension of Inbar and Lammers (2012) found that willingness to discriminate against one's ideological 7 opponents (which they found among social psychologists) extended to academics across the disciplines (Honeycutt & Freberg, 2017).…”
Section: Who Becomes An Academic Social Scientistmentioning
confidence: 91%
See 1 more Smart Citation
“…We summarize additional studies here that were not included in their review as further evidence supporting their perspective. A replication and extension of Inbar and Lammers (2012) found that willingness to discriminate against one's ideological 7 opponents (which they found among social psychologists) extended to academics across the disciplines (Honeycutt & Freberg, 2017).…”
Section: Who Becomes An Academic Social Scientistmentioning
confidence: 91%
“…For example, referring to women in STEM, Dasgupta and Stout (2014, p. 24) argue that "Young adults identify with successful female role models whose presence allows them to think: 'If she can be successful, so can I' and 'I want to be like her.'" Given the support for the gender similarity hypothesis (Hyde, 2005), we know of no reason to believe that this sort of social psychological process is unique to women, and there are many to think that they probably apply widely (Reinero, 2019), including to political role models in the social sciences (Honeycutt & Freberg, 2017;Honeycutt, Jussim, & Freberg, 2019). If non-liberal students do not have faculty who share their beliefs and values, this may dissuade some from furthering their studies, and from pursuing academic careers (Redding, 2012).…”
Section: Who Becomes An Academic Social Scientistmentioning
confidence: 99%
“…When it comes to bias and discrimination against conservatives, however, this is less likely. The point is illustrated by the data introduced above (e.g., Honeycutt & Freberg, 2017;Schwitzgebel, 2008;Yancey, 2011). They suggest that an aversion against conservatives is considered less objectionable in philosophy.…”
Section: Ideological Bias Is Viewed As Less Problematicmentioning
confidence: 98%
“…However, their study has various shortcomings, see Shields and Dunn (2016, p. 76f ) for details. 7 For weaknesses with the study and a partial replication, see Honeycutt and Freberg (2017).…”
Section: Ideological Demographics In Philosophymentioning
confidence: 99%
See 1 more Smart Citation